The duty of candour and the NHS agenda. Issue 2 (14th April 2020) - Powell, Martin
Abstract : Purpose: The purpose of the study is to explore how the duty of candour got onto the agenda of the British National Health Service. Design/methodology/approach: The conceptual approach is based on multiple streams approach, with the methodology being interpretive content analysis, which uses a deductive approach that focuses on both manifest and latent content. Findings: The duty of candour got onto the NHS agenda as a result of the Mid Staffordshire inquiry report and the long-term "interest group" campaign associated with Robbie's Law. It is argued that the "focusing event" of the Mid Staffordshire Inquiry Report opened the "policy window". It also highlights the importance of "policy entrepreneur" Sir Robert Francis whose "claim to a hearing", "political connections" and "persistence" was vital. Research limitations/implications: Analysis was confined to published documents. Originality/value: It highlights some of the factors that suggested why the duty of candour got onto the NHS agenda when it did.